MEDIA PEMBELAJARAN PADA KASUS PERTOLONGAN PERTAMA (STUDI KASUS SMP N 8 KOTA JAMBI) - Adhiatma, Novri (JURNAL AKADEMIKA, 2017)
Exciting learning is the first step toward achieving quality learning outcomes. One of the alternatives to get a fun learning for students is by using multimedia-based learning media using Adobe Flash Cs4 Applications. Based on interviews with teachers as a leader in SMP Negeri 8 Kota Jambi it is known that there are some problems encountered related to the practice of motion on the red cross, the observation material hard to find, due to lack of interactive media in the school. Difficulty observing, students who tend to be passive and less actively thinking. Based on these problems, the researcher made the Application of Learning Media First Aid Based Multimedia Cases which is the integration between images, video, material and simulation on motion competence in high level plants. By designing this application is expected to help increase interest in learning from the students, then able to receive the lessons well.